O direito fundamental de liberdade da convivência familiar e comunitária da criança e do adolescente - Pereira, José Antônio Borges (2008)
The present work tries to show the importance of the children's and adolescents Family and Community Coexistence, which is considered, nowadays, one of the fundamental rights of this significant portion in the Brazilian population. This insertion in the child's and adolescents constitutional system was introduced with an independent micro system with its own principles causing the appearance of a new branch of the law, which intends to preserve the common and fundamental rights of any person and other special fundamental rights due to the fact that they are considered people under development. With this new view, the children and the adolescents are entitled of freedom of family and community coexistence with their natural family and only for serious reasons according to the law, the family power can be breached. In this case the substitutive family will always supply the lack of this fundamental right preserving to the maximum the closer relationship bonds through the guard, tutoring and also the adoption, that makes a new family without any differentiation of a natural family. This way the children's and adolescents institutionalization must be admitted in exceptional and precarious instance, not as the definitive solution for social accommodation, because it is the family, society and Estate s obligation to empower the family and social bows or, as a last resource, find substitutive families in order to avoid the orphanages. In this aspect it is important to have a law system for children and adolescents committed to solve the processes which are related to the family and community coexistence, mainly if they are institutionalized children and adolescents, because the longer the social and familiar isolation period is, the bigger are the psychosocial consequences